ISLAM DAN MODERASI BERAGAMA DALAM PERSPEKTIF HADITS - Faelasup, Faelasup (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2021)
Religious moderation is a tolerant attitude and recognizes compromise in seeing differences. This research makes an inventory of the hadiths related to religious moderation with the word وسطيه which means moderation. From the search for كتب التسعة, the word وسطيه was not found, but there are several words that are equivalent to وسطيه namely القصد and الاعتدال. The word القصد is mentioned 6 times. Meanwhile, the word الاعتدال is only found once in the 255th Hadith Tirmidhi. The principle of wasathiyah described in the hadith is Al-khairiyah (chosen or best), Al-‘adalah (fair attitude), Al-Tawazun (balance). Attasamuh (tolerant). Al-Istiqamah (Consistency), Raf al-halaj (eliminating difficulties). Keywords Islam, Religious Moderation, Hadith